Absolute honesty : building a corporate culture that values straight talk and rewards integrity - Johnson, Larry, 1947- (AMACOM, American Management Association, 2003)
WorldCom. Enron. Tyco. Shocking accusations of dishonesty and silent complicity have dominated headlines recently, and cost the American economy trillions of dollars. Clearly, dishonesty doesn't pay. Drawing from these stories, as well as from more positive ones, Absolute Honesty shows how to establish and maintain a culture where honest communication is the norm, and employees can speak openly without fear of retribution. The book illustrates the impact that truthfulness and accountability can have on organizations, attacking the sort of passivity that allows little lies to grow into giant di.
Keywords: Corporate culture -- Moral and ethical aspects.; Communication in organizations -- Moral and ethical aspects.; Corporations -- Moral and ethical aspects.; Business ethics.; Honesty.; elektronické knihy; electronic books